2019
DOI: 10.1093/neuros/nyz312
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Standardized Multimodal Postoperative Analgesia Protocol Improves Pain Control, Reduces Opioid Consumption, and Shortens Length of Hospital Stay After Posterior Lumbar Spinal Fusion

Abstract: BACKGROUND Multimodal analgesia regimens have been suggested to improve pain control and reduce opioid consumption after surgery. OBJECTIVE To institutionally implement an evidence-based quality improvement initiative to standardize and optimize pain treatment following neurosurgical procedures. Our goal was to objectively evaluate efficacy of this multimodal protocol. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
0
15
1
9
Order By: Relevance
“…Poor postoperative pain control is observed in 57% of patients following elective spine surgery [208]. Inadequate acute pain control is associated with the development of chronic pain and significant systemic inflammatory response leading to organ dysfunction and pain [209,210]. A standardized perioperative multimodal antinociceptive protocol results in adequate postoperative pain relief and improved outcomes [5].…”
Section: Postoperative Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Poor postoperative pain control is observed in 57% of patients following elective spine surgery [208]. Inadequate acute pain control is associated with the development of chronic pain and significant systemic inflammatory response leading to organ dysfunction and pain [209,210]. A standardized perioperative multimodal antinociceptive protocol results in adequate postoperative pain relief and improved outcomes [5].…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…Opioids are effective in treating acute postoperative pain following spinal surgery [210]. However, opioid-sparing techniques are important and should be applied in ERAS pathways to allow patients to recover early and reduce complications related to opioid use [210].…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…70,71 Less consistently included are muscle relaxants such as methocarbamol or diazepam and local anesthetics such as transdermal lidocaine patches that function via prolonging the inactivation of sodium channels within the cell membrane of neurons. 72 While multimodal approaches have previously been used in orthopedic surgery and other surgical fields, recent research has investigated the use of multimodal approaches involving these drugs specifically in postoperative pain for spine surgery. A multimodal regimen consisting of scheduled doses of acetaminophen, NSAIDs, gabapentin, lidocaine patches, and one of two muscle relaxants was compared to a non-standardized provider-dependent regimen in one retrospective cohort after posterior lumbar surgery.…”
Section: Prescription Medications and Multimodal Pain Regimensmentioning
confidence: 99%
“…Unfortunately, documentation of postoperative pain scores was not consistent, resulting in missing data. A QI initiative implemented by Walker et al 20 with 220 patients undergoing lumbar fusion demonstrated a decrease in hospital LOS after implementation of an MMA protocol. However, our QI project resulted in no significant change in either facility or PACU LOS.…”
Section: Discussionmentioning
confidence: 99%